Calcination‐Dependent Surface Defect Variation and Antibacterial Activity of Magnesium Oxide Nanoplates. Issue 11 (17th March 2020) - Li, Xiaoyi; Zhao, Jiao; Hong, Xiaoyu; Yang, Yan; Tang, Xiaojia; Zhu, Yimin; Li, Tie
Abstract: Nanostructured magnesium oxide (MgO) is a new kind of environment‐friendly antimicrobial agents with high efficiency, non‐toxicity and relatively low cost. Herein, MgO nanoplates were synthesized by a simple hydrothermal‐calcination method. Antibacterial test showed that the MgO nanoplates calcinated at 450 °C performed the best antibacterial activity, with the antibacterial ratio higher than 99.9 % against Escherichia coli . Based on the results of structural characterization and superoxide radical ( . O2 − ) detection, the excellent antibacterial activity of MgO was attributed to the high content of oxygen vacancies, which could result in more . O2 − production. In addition, the MgO nanoplates exhibited good antibacterial performance at low concentration, and also performed long‐term antibacterial activity. Our method provides a strategy for regulation of surface defects and improvement of antibacterial activity on the pure MgO nanoplates. Abstract : This study investigated the influence of calcination temperature on the surface characterization and antibacterial activity of the MgO nanoplates synthesized by a facile hydrothermal‐calcination method. Surface defects concentration would ensure more . O2 − generation and effectively enhance the antibacterial activity of the MgO nanoplates.